PERAN DUKUNGAN ORANG TUA DAN SELF-EFFICACY DALAM MENINGKATKAN MOTIVASI BELAJAR PESERTA DIDIK - Theophanny Rampisela; Criezta Korlefura; Hendra Suhry (CV. ADIBA AISHA AMIRA, 2025)
This study aims to analyze the role of parental support and self-efficacy in enhancing students’ learning motivation at the secondary education level. Using a descriptive qualitative approach, data were collected through in-depth interviews, classroom observations, and documentation involving students, parents, and teachers. The findings reveal that parental support encompassing emotional, academic, and instrumental aspects plays a significant role in strengthening students’ motivation to learn. Students who receive consistent encouragement, guidance, supervision, and adequate learning facilities from their parents demonstrate higher intrinsic motivation and greater engagement in academic activities. Furthermore, self-efficacy emerges as a crucial internal factor influencing students’ persistence, optimism, and willingness to face academic challenges. The study also highlights that parental support contributes to the development of students’ self-efficacy, thereby creating a reinforcing effect on learning motivation. These results indicate that students’ motivation is shaped through the interaction between external factors (parental support) and internal factors (self-efficacy). This study suggests that efforts to enhance learning motivation should involve collaborative roles between families and schools, alongside strategies to strengthen students’ academic confidence in order to foster an optimal learning environment.